Role of Natural Zeolite (Clinoptilolite) on the Biochemical Blood Parameters and Liver Enzymes of Common Carp (Cyprinus carpio L.) Reared in Recirculation Aquaculture System - Mohammed Hamed Farhan and Ahmed Salahudeen Naser (مجلة الانبار للعلوم البيطرية, 2024)
The aim of conducting this study was to evaluate the use of added natural zeolite (clinoptilolite) in common carp fingerling (Cyprinus carpio L.) breeding ponds and to demonstrate its effect on biochemical blood parameters and liver enzymes, This study was conducted for 12 weeks with an initial weight of the fish reachin (25 ± 1) gram, The study divided into Seven treatments, each treatment was divided into 3 replicates, in each replicate (10 fish), the first treatment (control treatment) Without adding zeolite, Zeolite was added to the rest of the treatments in two ways, the first way was (add inside the filter) in proportions (5,10,15) g/L for the second, third, and fourth treatments, respectively, In the second way, add zeolite (inside the rearing ponds with plastic mesh bags) in proportions (5,10,15)g/L for the fifth, sixth, and seventh treatments, respectively, The results of the study showed The fifth treatment recorded the highest values for biochemical blood parameters (CHO, NHDL, Sugar, Cortisol) when compared to the rest of the experimental treatments The results of the study showed The fifth treatment recorded the highest values for biochemical blood parameters (CHO, NHDL, Sugar, Cortisol) when compared to the rest of the experimental treatments, The best ratios for adding natural zeolite (Clinoptilolite) were (5, 15) g/L zeolite in the biofilter and (10, 15) g/L zeolite in the fish tanks, as these ratios gave the best values for the blood biochemical indicators of the common carp that were used in the experiment (CHO, T.G, NHDL, sugar, protein, albumin, ALT and cortisol) compared to the rest of the Studied standards. [AJVS 2024; 17(2.000): 64-70]